End-of-Pipe or Cleaner Production? An Empirical Comparison of Environmental Innovation Decisions Across OECD Countries - Manuel Frondel; Jens Horbach; Klaus Rennings (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
While both fundamental types of abatement measures mitigate the adverse environmental impacts of production, cleaner production technologies are frequently more advantageous than end-of-pipe technologies for environmental and economic reasons. This paper analyzes a variety of factors that might enhance firms? propensity to implement cleaner products and production technologies instead of end-of-pipe technologies. On the basis of a unique facility-level data set derived from a recent OECD survey, we find a clear dominance of cleaner production in seven OECD countries: Surprisingly, 76.8% of the facilities report that they invest predominantly in cleaner production technologies. With regard to environmental product innovations, the large majority of facilities reports that the measures they have undertaken to reduce environmental impacts were geared at production processes and not so much at products. Our estimation results are based on multinomial logit models which indicate that regulatory measures and the stringency of environmental policies are positively correlated with end-of-pipe technologies, while cost savings, general management systems, and specific environmental management tools tend to favor clean production. We conclude that improvements towards cleaner products and production may be reached by the continuous development and wider diffusion of these management tools. Improvements may also be stimulated by widening the cost gap between the two types of technologies, for instance, by additionally charging for waste and energy use.
Keywords: O33; C25; Q55; O38; 330; Cleaner production; end-of-pipe-technologies; technological innovation; technological change; government policy; discrete choice models; Umweltschutzinvestition; Umweltmanagement; Umwelttechnik; Umweltauflage; Diskrete Entscheidung